Root and root canal morphology of permanent mandibular first and second molars in a Kuwaiti population: A retrospective cone-beam computed tomography study - Humoud S. Alazemi; Saad A. Al-Nazhan; Mazen A. Aldosimani (Saudi Dental Journal)
Aim: Endodontic diseases typically affect the mandibular molars. Understanding the complex morphology of the root canal system and its variations is necessary for successful endodontic treatment. The aim of this study was to evaluate the morphology of roots and root canals of mandibular first and second permanent molar teeth in a Kuwaiti population using cone-beam computed tomography (CBCT). Materials and methods: CBCT images of 651 mandibular first and second molar teeth were obtained from specialist government dental centers. The age, sex, root canal configuration, and number and type of roots were recorded. The data were statistically analyzed. Results: The most common canal configuration in the mandibular first and second molars was type II (65.6% and 54.4%, respectively), with no significant difference seen between the sexes (p = 0.234). The canal configuration was significantly different between the mandibular first and second molars (p < 0.001). Most teeth had two roots (94.5%); split roots were common (92.6%) and the number thereof varied significantly. Radicular grooves were most common on the lingual side (4.9%). C-shaped canals were present in 43 (6.60%) teeth. Additionally, one tooth had a confluent middle mesial canal and nine (1.4%) had radix entomolaris. Conclusion: Mandibular molars in our Kuwaiti population typically had two split roots with type II and IV canal configurations. The prevalence rates of C-shaped canals, middle mesial canals, and radix entomolaris were remarkably low.